Clonal reproduction by seed of a cultivated hybrid plant: a new perspective for small-scale rice growers - Vernet, Aurore; Meynard, Donaldo; Guiderdoni, Emmanuel (Comptes Rendus Biologies)

(untitled)
Transferring an asexual mode of reproduction by seeds (apomixis) to cultivated plants would enable clonal reproduction of heterozygous genotypes such as F1 hybrids with hybrid vigor (heterosis), facilitating their access and multiplication by small-scale growers. Although sources of apomixis and the genetic loci controlling its constituent elements have been identified in wild species, their transfer by crossing to cultivated species has so far been unsuccessful. Here, we have introduced synthetic apomixis in hybrid rice to produce a high (95–100%) frequency of clonal seeds, via the inactivation of three meiotic genes—resulting in unreduced, non-recombined gametes—and the addition of an egg cell parthenogenesis trigger. The genotype and phenotype, including grain quality, of the F1 hybrid are reproduced identically in the clonal apomictic progenies. These results make synthetic apomixis compatible with future use in agriculture.